The Salesian School Administrator - Rodríguez López, Antonio (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2024)
Don Bosco’s writings analyse the main features of the Salesian director and his relationship with other educational agents. The importance of good and productive financial management, marketing in the recruitment of students, religious experience, the sense of belonging to the Salesian school, empathy, closeness, affection... are essential qualities of those who exercise leadership in a Salesian school, which has different characteristics from those managers and directors of other educational entities. the Salesian school needs those who are best able to exercise management.